SST2 is a promising biomarker in hypertensive patients undergoing renal denervation. (25th November 2020) - Topf, A; Paar, V; Grueninger, J; Wernly, B; Weber, T; Mahfoud, F; Lichtenauer, M; Hoppe, U; Brandt, M; Motloch, L.J
Abstract: Introduction: Therapy resistant arterial hypertension (raHTN) is a major clinical burden. While therapeutic alternatives are still missing, novel interventional procedures like renal denervation (RD) are still evolving. Indeed, despite discoursing results of the Simplicity HTN-3 trial, new promising results resulted in a revival of this procedure. Therefore, predictors for the success of future interventions would be of great clinical benefit. The novel biomarker sST2 shows promising results for risk stratification of cardiovascular patient. While, sST2 belongs to the IL-1 receptor family, it has an influence on immunologic processes with consequent cardioprotective effects including prevention of myocardial hypertrophy and fibrosis indicating predictive potential in hypertensive heart disease. Nevertheless, clinical implementation of this promising biomarker was not investigated in patients with raHTN undergoing RD. Purpose: To investigate a potential clinical relevance of sST2 in patients with raHTN undergoing RD. Methods: We evaluated 58 patients with raHTN (age: 63±11 years, systolic blood pressure at baseline: 178±24mmHg) undergoing bilateral RD. If available, serum levels of sST2 were analyzed at baseline as well as at follow-up at one and/or three month. Results: While RD was able to decrease blood pressure levels after one month (systolic blood pressure at one month: 158±21mmHg, p<0.01), on echocardiography a reduction of left ventricular mass (LVM) was observed at one month with a further significant reduction at three month (LVM at baseline: 233±68g, LVM at one month: 218±59g and LVM at three month: 181±59, p<0.01). This observation was accompanied by a significant decrease of sST2 levels at three month (sST2 baseline: 6322±3578pg/ml vs. sST2 three month: 4704±1586pg/ml, p=0.02). Furthermore, baseline sST2 was positively correlated with systolic blood pressure at one month, measured either at office (r=0.57, p<0.01) or invasively in the aorta (r=0.49, p=0.03) indicating a potential predictive value of this biomarker. Conclusion: In patients with raHTN, RD is associated with a significant decrease of sST2 levels, indicating sST2 to be involved in remodeling processes after RD. Furthermore, sST2 levels at baseline might be a potential predictor of intervention success of RD. Further, studies need to investigate the association of sST2 levels and RD. Funding Acknowledgement: Type of funding source: None